Integrated Project Management Sourcebook A Technical Guide to Project Scheduling, Risk and Control - Vanhoucke, Mario (Springer International Publishing : Imprint: Springer, 2016)
This handbook is a unique, comprehensive resource for professional project managers and students in project management courses that focuses on the integration between baseline scheduling, schedule risk analysis and project control, also known as Dynamic Scheduling or Integrated Project Management and Control. It contains a set of more than 70 articles. Each individual article focuses on one particular topic and features links to other articles in this book, where appropriate. Almost all articles are accompanied with a set of questions, the answers to which are provided at the end of the book. This book is accompanied by and is based on the Project Management Knowledge Center (www.pmknowledgecenter.com), an online learning platform for Integrated Project Management.